2020
DOI: 10.1016/j.jot.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of large chronic rotator cuff tear can benefit from the bone–tendon composite autograft to restore the native bone–tendon interface

Abstract: Purpose We designed a paired controlled study to investigate the advantages of using bone–tendon composite autograft to reconstruct chronic rotator cuff tear compared with primary repair and provide some evidence to use the bone–tendon composite autograft. Method Thirty-eight Sprague–Dawley rats were used. The native bone–tendon junctions of supraspinatus and Achilles tendon insertion from two rats were harvested for gross and histological observation. Another thirty-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Ficklscherer, A [ 124 ] found that comparing autologous Achilles tendon bursa tissue with simple suture, the former resulted in higher content of collagen Ⅱ in the repaired site. Sun, Y [ 125 ] demonstrated that the bone-tendon composite autograft group had a higher tendon maturity score than simple suture. Chen, Y [ 126 ] discussed the stem cell sheets derived from urine of the patient, and the comparison with the tendon-bone suture showed that the cell sheet group presented more collagen fibers at the tendon-bone interface.…”
Section: Resultsmentioning
confidence: 99%
“…Ficklscherer, A [ 124 ] found that comparing autologous Achilles tendon bursa tissue with simple suture, the former resulted in higher content of collagen Ⅱ in the repaired site. Sun, Y [ 125 ] demonstrated that the bone-tendon composite autograft group had a higher tendon maturity score than simple suture. Chen, Y [ 126 ] discussed the stem cell sheets derived from urine of the patient, and the comparison with the tendon-bone suture showed that the cell sheet group presented more collagen fibers at the tendon-bone interface.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there have been a number of promising new advances and strategies for the enhancement of tendon-bone healing. For example, novel decellularised matrix scaffolds with a special structure have shown the advantage of improved enthesis regeneration [ 52 , 53 ]. Some researchers proposed a book-shaped acellular scaffold by sectioning the natural fibrocartilage to fabricate a book-shaped decellularised matrix scaffold, which displayed an excellent capability of cell delivery and inducibility of fibrocartilage formation [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, creating a large segmental defect in the rat SSPT posed a considerable challenge. Despite the rat's SSPT having a total length of approximately 16.2 mm [ 67 ], the majority of the tendon is embedded within the supraspinatus muscle, resulting in less than 3.5 mm of exposed tendon length [ 41 , 68 ]. Due to the small size of the rat SSPT, our assessment options are limited to employing a bone-to-tendon defect approach to assess the therapeutic effect of the BioTenoForce scaffold.…”
Section: Discussionmentioning
confidence: 99%